Identification of flow mark defect on haitian MA 1200 machine in the molding process at PT. Philips Industries Batam - Juwita, Erna; Purba, Adi Syahputra; Simanjuntak, Jefri Kemri Rodi Samuel; Br. Manurung, Agnes; Mutiarani, Mutiarani (International Journal of Mechanical Computational and Manufacturing Research, 2025)
PT Philips Industries Batam is a company engaged in the manufacturing sector. One of the production processes carried out at PT Philips Industries Batam is the molding process. In the industrial world, the molding process has several types of defects that can affect product quality. The highest number of defects was identified to find the root cause using the Pareto and Fishbone diagram. This research aims to identify the factors causing the defect. Parameters on the Haitian MA 1200 machine were identified to determine the cause of the flow mark defect, thereby improving the quality level of the produced products. From five trials, the optimal parameter setting value was found in the fifth trial. The parameter settings consist of the start post: inject 1 with a value of 63, inject 2 with a value of 42, pressure: inject 1 with a value of 165, inject 2 with a value of 155. Pressure: hold 1 with a value of 55, hold 2 with a value of 45, and flow: hold 1 with a value of 18 and hold 2 with a value of 13. The flow mark defect on the Haitian MA 1200 machine effectively decreased by adjusting certain parameters.